Growth Hormone Deficiency Impairs Blood Clotting and Reduces Factor VII Coagulant Activity in Rat - Sävendahl, L S G; Grankvist, K; Engström, K G (Thrombosis and Haemostasis, 1995)
To investigate pituitary effects on the vitamin K-dependent coagulation factors, female rats were hypophysectomized (hypox) and treated with growth hormone (GH), cortisone, thyroxine, vitamin K, or saline. After 11 days of treatment, the prothrombin time, platelet count, and factors II, VII, IX, and X were determined. The prothrombin time was 52.9 ± 1.2% for control rats and 39.1 ± 0.8% for hypox rats (mean ± SEM; p<0.001). All factors decreased after hypophysectomy, reaching significance for factor VII (from 264 ± 23% to 131 ± 9%; p <0.001) and factor IX (from 28.4 ± 2.2% to 17.1 ± 2.5%; p<0.01) while the platelet count was unaffected. When hypox rats were treated with GH, the prothrombin time increased to 50.9 ± 1.0% (p <0.001) and factor VII to 299 ± 10% (p<0.001). Factor II, IX, and X were slightly increased after GH substitution but not after cortisone, thyroxine, or vitamin K treatment. To summarize, GH is of importance for normal hemostasis in the female rat.